Dynamic Gene Expression and Alternative Splicing Events Demonstrate Co-Regulation of Testicular Differentiation and Maturation by the Brain and Gonad in Common Carp - Zhao, Yuanli; Chen, Kuangxin; Liu, Fei; Jiang, Mouyan; Chen, Zonggui; Chen, Huijie; Song, Yanlong; Tao, Binbin; Cui, Xuefan; Li, Yongming; Zhu, Zuoyan; Chen, Ji; et al. (Frontiers in Endocrinology, 2022)
The common carp (Cyprinus carpio) accounts for approximately 10 % of the annual freshwater aquaculture production and is an ideal model to study cyprinidae reproduction. Female common carp grow faster than the males; therefore, related research presents an opportunity with high application value. Although we have a detailed understanding of common carp’s early gonadal differentiation process, information about genome-wide gene expression, regulation, and underlying molecular mechanisms during this process remain limited. Here, time-course data comprising six key stages during testicular differentiation and maturation were investigated to further understand the molecular mechanisms underlying the testicular development in cyprinid species. After integrating these time-series data sets, common carp genome, including 98,345 novel transcripts and 3,071 novel genes were re-annotated and precisely updated. Gene co-expression network analysis revealed that the ubiquitin-mediated proteolysis pathway was essential for metabolism during testicular differentiation in the endocrine system of C. carpio. Functional enrichment analyses indicated that genes mainly related to amino acid metabolism and steroid hormone synthesis were relatively highly expressed at the testicular undifferentiation stages, whereas genes associated with cell cycle and meiosis were expressed from the beginning of testicular differentiation until maturation. The dynamics of alternative splicing events demonstrated that exon skipping accounted for majority of the alternative splicing events in the testis and the brain during gonad development. Notably, several potential male-specific genes (fanci and sox30) and brain-specific genes (oxt, gad2, and tac1, etc.) were identified. Importantly, we traversed beyond the level of transcription to test for stage- and gonad-specific alternative splicing patterns between the brain and testis. This study is the first to describe a comprehensive landscape of alternative splicing events and gene expression patterns during gonadogenesis in common carp. This work is extremely valuable to elucidate the mechanisms underlying gonadal differentiation in Cyprinidae as well as other fish species.